2022
DOI: 10.1097/xcs.0000000000000143
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Surgical Outcomes after Postmastectomy Breast Reconstruction

Abstract: BACKGROUND: Women of color with breast cancer are less likely to undergo post-mastectomy reconstruction compared with White women, but it is unclear whether their perioperative outcomes are worse. The goal of this study was to investigate differences in preoperative comorbidities and postoperative complications by race/ethnicity among women with breast cancer undergoing postmastectomy reconstruction. STUDY DESIGN: Data were collected from the National I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Existing research on skin color in the field of plastic surgery has shown that it can be an important factor not only in health equity but also in the prevalence of disease, patient risk for certain conditions, and patient outcomes, 2,[16][17][18] but such investigations are hindered by difficulty collecting objective and consistent data on skin color. It has been reported that plastic surgery journals use significantly more images of white-skinned than dark-skinned individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research on skin color in the field of plastic surgery has shown that it can be an important factor not only in health equity but also in the prevalence of disease, patient risk for certain conditions, and patient outcomes, 2,[16][17][18] but such investigations are hindered by difficulty collecting objective and consistent data on skin color. It has been reported that plastic surgery journals use significantly more images of white-skinned than dark-skinned individuals.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Black women undergoing breast surgery are more likely to have longer lengths of stay, develop POCs, and experience higher in-hospital mortality than White women. 6,7 Similarly, patients living in areas of high deprivation report poorer psychosocial well-being and physical functioning after breast surgery than their counterparts living in areas with less deprivation. 8 A plausible explanation for these racial and socioeconomic disparities in postoperative outcomes is an interplay between greater rates of comorbidities and higher socioenvironmental stressors (e.g., low socioeconomic status) often experienced by marginalized and minoritized women.…”
Section: Introductionmentioning
confidence: 99%
“…1,16 Previous research analyzing predictors of postmastectomy complications have primarily focused on individual-level risk factors (e.g., BMI, diabetes, age, and medical comorbidities), 7 with few examining the influence of economic deprivation 22,26 and racial/ethnic disparities. 27 However, there is a lack of research regarding the influence of geographic disparities, such as rural status, and structural community…”
mentioning
confidence: 99%